Considering Students’ Propensity of Divergent or Convergent in Executing Science Project - Ardiana Sholehah; Baiq Asma Nufida; Habibi Habibi; Ika Nurani Dewi; Yusran Khery (Postgraduate, University of Mataram, 2024)
This study examines student performance in project-based learning by assessing their tendencies toward divergent or convergent thinking. A questionnaire was developed to help teachers identify and maximize the thinking potential of individual students during the learning process. The research involved 149 junior high school students from West Lombok for validity and reliability testing and 84 respondents for the categorization trial. Instruments were validated by experts using descriptive methods and percentage scores. Validity was determined through product moment correlation coefficients, while reliability was assessed using alpha reliability coefficients. Categorization utilized non-level (nominal) categorization methods. The study employed a pre-experimental approach with a one-shot case study design, involving 33 eighth-grade students in a local natural pesticide project. Student performance was evaluated through practical skill assessments and comprehensive portfolios. Data analysis used percentage and comparative statistical methods. Results showed the questionnaire contained 40 items—20 each for divergent and convergent thinking—with an expert validation score of 89.50, rated excellent. All items were valid, with correlation values exceeding the critical threshold (rtable = 0.16). Reliability scores were high for divergent and convergent groups (0.64 and 0.72) and satisfactory for all items (0.55). The questionnaire effectively categorized up to 20% of subjects into divergent and convergent groups. The study revealed significant performance differences between the two groups and recommends mixing students with divergent and convergent propensity in group projects to enhance outcomes.